MICROCREDIT FINANCIAL INSTITUTIONS IN THE FUNCTION OF ENTREPRENEURSHIP DEVELOPMENT - Aničić, Dusan; Simić, Nataša; Petrović, Vesna (Journal of process management and new technologies, 2018)
High unemployment rate, low competitiveness level, high level of foreign debt and low GDP per capita are all basic indicators of (un)developed economy in Serbia, present throughout the period of transition. Since large economic systems, especially in industry and agriculture, have been completely devastated in the transitional period, entrepreneurship model is imposed as the most efficient type of economic development and connection to the developed countries. One of the greatest obstacles to successful entrepreneurship development in Serbia is funding conditions dominated by the banking sector, and the rest of the funding types appropriate for the entrepreneurs' true needs are largely neglected. The creation of adequate legislation for microcredit institution development that would primarily finance entrepreneurship and family business development would have a significant positive effect on the development of this sector.